Pemberdayaan Masyarakat Berbasis Potensi Lokal melalui Pelatihan Produksi dan Pemasaran Dodol Labu Siam - Miki Wijana; Mochamad Rifky Wijaya Wijaya; Yuli Nurholiza Nurholiza; Rindi Antika (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
This Community Service (PKM) was conducted in Tenjolaya Village with the aim of enhancing the community’s skills in processing local agricultural products, particularly chayote, into value-added food products such as dodol labu siam (chayote dodol). The main problems faced by the local community include limited knowledge of hygienic production techniques, attractive and standardized packaging, as well as modern digital marketing strategies. Using a community-based training approach, the program was carried out in several stages, including needs assessment, material design, training in production and packaging, online marketing training, and monitoring and evaluation. The results show that participants successfully improved their skills in producing higher quality dodol labu siam, designing more modern and appealing product packaging, and utilizing social media and e-commerce platforms to expand market reach. This program also had a positive impact on motivating the community to develop local-based businesses and strengthen product competitiveness in the digital era. Therefore, this PKM initiative contributed to empowering the village economy through local food product innovation and the digital transformation of micro, small, and medium enterprises (MSMEs).